ANALISIS KESESUIAN BUKU AJAR TEMA INDAHNYA KEBERSAMAAN KELAS IV SD DENGAN KURIKULUM 2013 - Novia Nur Estiningtyas; Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract: This research aims to determine the suitability of text book grade IV Elementary School theme of Wonderful Togetherness with core competencies in the curriculum of  2013. Type of this research is a descriptive qualitative content analysis in the form of. The object of this research is to text book grade IV Elementary School theme of Wonderful Togetherness. Data retrieval is done in this study use techniques of observation and engineering library. Research instrument is the researchers themselves, researchers analyze to text book grade IV Elementary School theme of Wonderful Togetherness publisher by Kemendiknas. The results of showed that not all the material on the subjects presented in the book grade IV Elementary School theme of Wonderful Togetherness complies with curriculum of 2013. Some of the lesson have yet to charge according to the curriculum of 2013 is Civic Education  (PKn), Art and Culture and Creating Handicraft (SBdP), Mathematics (Matematika) and Sport Physical Education and Health (PJOK) in sub theme 1 is Cultural Diversity My People. While on sub theme 2 Togetherness in Diversity  that is not in accordance with the curriculum is Art and Culture and Creating Handicraft (SBdP), Indonesian (Bahasa Indonesia), Mathematics (Matematika), and Sport Physical Education and Health (PJOK). And sub theme 3 Am Grateful for Diversity is Art and Culture and Creating Handicraft (SBdP), Social Sciences (IPS), and Mathematics (Matematika).